Consumo de agua durante la cría de mosca soldado-negra, Hermetia illucens - Elena, Fernando (2025)
In a closed system with photoperiod, temperature and ambient humidity regulation, water consumption and the performance of BSF cultivation in three different organic substrates were evaluated during the entire productive phase of the black soldier fly (BSF) in the FAUBA insectary. Therefore, the water consumed to prepare the feed, to control the ambient humidity and for cleaning was quantified. Our results show that the main water consumption is related to the maintenance of insectary. We have established that the percentages of feeding moisture and ambient humidity are key factors for the \ndevelopment of this fly. The water consumption to produce 1 kg of BSF biomass was lower than the values reported in the literature for bovine, porcine or poultry production. \nOnce the key parameters for BSF production are well defined, production schemes can be put together that reduce the pressure on the planet's resources as much as possible, achieving increasingly sustainable production.